Assessment of Regional Innovation Systems as an Assumption for Innovation Policy Adjustment - Vladimír ŽÍTEK; Viktorie KLÍMOVÁ; Maria KRÁLOVÁ (Transylvanian Review of Administrative Sciences, 2016)
The role of regions in promoting innovation is gaining increasing signifi cance. For a policy to be effi cient, it is fi rst necessary to analyze the innovation performance and the character of the innovation system. The aim of this paper is to propose and implement a methodology for the evaluation of regional innovation systems using the index of the regional innovation system (IRIS) devised by the authors. The analysis is performed using the example of Czech NUTS3 regions. The evaluated indicators were divided into fi ve groups (factors): Knowledge, Businesses, Intellectual property, Political support, and Results. Based on the standardization and rescaling of the factors, the IRIS was calculated. The regions were divided into groups by means of the cluster analysis. The highest value of the IRIS was achieved by Capital City Prague, followed by the South Moravian region. The lowest value was achieved by the Karlovy Vary region.